Revitalisasi Bank Sampah Sekolah dalam Mendesain Model Pendidikan Lingkungan Berkelanjutan Berbasis Teknologi Tepat Guna - Budiaman; Aam Amaningsih Jumhur; Ahmad Kholil; Astri Febry Susanti (Bahasa Indonesia, 2022)
Abstract This Integrated Community Service Activity Real Work Lecture aims to revitalize school waste banks in designing sustainable environmental education models based on appropriate technology. Environmental education is expected to be obtained by junior high school students through the waste bank extracurricular program. Environmental education to be achieved is focused on managing and utilizing waste to produce environmental products into strategic activities that can be developed, in collaboration with successful waste banks. The method of implementation is in the form of observation and FGD conducted in SMP Negeri 9 and SMP Negeri 21 Bekasi City. Through this activity, various problems experienced by SMP Negeri 9 and SMP Negeri 21 Bekasi City were formulated in re-activating the school waste bank program. Based on the series of activities from FGD to simulation, it can be concluded that school leaders, environmental extracurricular coaches, and students of SMP Negeri 9 and SMP Negeri 21 Bekasi City really hope that waste management activities in their respective schools can be reactivated. Considering that the activities are still in a pandemic atmosphere, the reactivation of the school waste bank is carried out in conjunction with the restructuring of the extracurricular environmental management in their respective schools. Abstrak Kegiatan Pengabdian Kepada Masyarakat Terintegrasi Kuliah Kerja Nyata ini bertujuan untuk melakukan revitalisasi bank sampah sekolah dalam mendesain model pendidikan lingkungan berkelanjutan berbasis teknologi tepat guna. Pendidikan lingkungan diharapkan dapat diperoleh oleh siswa SMP melalui program ekstrakulikuler bank sampah. Pendidikan lingkungan yang ingin dicapai difokuskan pada pengelolaan dan pemanfaatan sampah sampai menghasilkan produk lingkungan menjadi kegiatan strategis yang dapat dikembangkan, bekerjasama dengan bank sampah yang sudah sukses. Metode pelaksanaan berupa observasi dan FGD yang dilakukan di SMP Negeri 9 dan SMP Negeri 21 Kota Bekasi. Melalui kegiatan ini dirumuskan berbagai permasalahan yang dialami oleh SMP Negeri 9 dan SMP Negeri 21 Kota Bekasi dalam mengaktifkan kembali program bank samapah sekolah. Berdasarkan rangkaian kegiatan dari mulai FGD sampai simulasi dapat disimpulkan bahwa pimpinan sekolah, Pembina ekstrakulikuler lingkungan, dan siswa SMP Negeri 9 dan SMP Negeri 21 Kota Bekasi sangat berharap agar kegiatan pengelolaan sampah di sekolah masing-masing dapat diaktifkan kembali. Mengingat kegiatan masih dalam suasana pandemi maka pengaktifan kembali bank sampah sekolah dilakukan bersamaan dengan restukturisasi pengurus ektrakulikuler lingkungan di sekolah masing-masing.